2020
DOI: 10.1371/journal.pone.0235871
|View full text |Cite
|
Sign up to set email alerts
|

The passage of time during the UK Covid-19 lockdown

Abstract: In March 2020, in response to the Covid-19 pandemic, the UK Government imposed social and physical distancing measures on the population. These lockdown measures caused significant changes to all aspects of daily life. The current study examined how the passage of time was distorted during the lockdown period. Using an online questionnaire, day and week passage of time judgments were collected. In addition, measures of affect, task load and satisfaction with current levels of social interaction were taken. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
220
4
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(277 citation statements)
references
References 51 publications
32
220
4
8
Order By: Relevance
“…The main consequence of these changes was that the participants' relationship to time was altered: Time seemed to pass far more slowly compared to before the lockdown. This feeling of a slowing down of time with the lockdown is a robust psychological phenomenon reported in all the international studies on the time judgment conducted during the lockdown (Cellini et al, 2020;Droit-Volet et al, 2020;Ogden, 2020;Torboli et al, 2020). However, the present studies investigating a large series of factors allowed us to identify the main causes of these changes in the subjective experience of time with the lockdown.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The main consequence of these changes was that the participants' relationship to time was altered: Time seemed to pass far more slowly compared to before the lockdown. This feeling of a slowing down of time with the lockdown is a robust psychological phenomenon reported in all the international studies on the time judgment conducted during the lockdown (Cellini et al, 2020;Droit-Volet et al, 2020;Ogden, 2020;Torboli et al, 2020). However, the present studies investigating a large series of factors allowed us to identify the main causes of these changes in the subjective experience of time with the lockdown.…”
Section: Discussionmentioning
confidence: 63%
“…One initial consequence is a profound upheaval in our relationship with time. Recent international surveys on the judgment of the passage of time (PoT) during the lockdown suggested that people have experienced a slowing down of time (Cellini et al, 2020;Droit-Volet et al, 2020;Ogden, 2020;Torboli et al, 2020). However, the different factors explaining this change in the experience of time during lockdown were not further analyzed in these initial surveys, which focused on a limited number of factors (e.g., stress, anxiety, social satisfaction, sleep disturbance).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the lack of social interaction has a more profound effect on people with higher income and education 62 . Lack of social interaction also has a negative impact as more time passes for older people, as evidenced by a large cross-sectional study in the UK 64 . Children have reported being more restless, irritable, and inattentive during the lockdown with increased screen time being the likely contributor 65 .…”
Section: Emotional Wellbeing and Social Connectednessmentioning
confidence: 99%
“…In the absence of vaccination and effective drugs, non-pharmaceutical PHIs are being considered as the only way to control COVID-19. Although many countries like the UK and the US have implemented multiple interventions to control the new epidemic [ 36 , 37 ], there is no doubt that the political, social, and geographical context has affected the success of any [ 38 , 39 ]. Nevertheless, it is not completely known which intervention(s), why, where, for whom, and how has been effective in slowing down the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%